2014
DOI: 10.1590/s1516-14392014005000056
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of geometric configurations and vibrational spectra in citric acid complexes

Abstract: The performance of advanced electronic ceramics is directly related to the synthesis route employed. Sol-gel methods are widely used for this purpose. However, the physicochemical intermediate steps are still not well understood. Better understanding and control of these processes can improve the final quality of samples. In this work, we studied theoretically the formation of metal complexes between citric acid and lithium or barium metal cations with different citric acid/metal proportions, using Density Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The two peaks at 1688 and 1742 cm –1 observed in the CA spectrum are associated with strongly and weakly or non-hydrogen-bonded CO groups, respectively. ,, A single CO stretch mode was observed in the CMCF-F- x spectra, which indicated that almost all of the CO groups in the hydrogel were involved in hydrogen bonds with similar strength. Similar peak shifts have been observed in theoretical calculations for anhydrous CA and CA complexes and in experimental results for the complex material of CMC and CA. , The CO stretching peak in the CMCF-F- x hydrogel spectra shifted to lower wavenumber with an increase in the CA concentration increased, i.e., from 1717 cm –1 for CMCF-F-0.05 to 1704 cm –1 for CMCF-F-2 (Figure b). The wavenumber of the CO stretching mode shifts downward owing to an increase in the hydrogen-bond strength. , Thus, the results indicate that the bond strength increased with an increase in the CA concentration.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The two peaks at 1688 and 1742 cm –1 observed in the CA spectrum are associated with strongly and weakly or non-hydrogen-bonded CO groups, respectively. ,, A single CO stretch mode was observed in the CMCF-F- x spectra, which indicated that almost all of the CO groups in the hydrogel were involved in hydrogen bonds with similar strength. Similar peak shifts have been observed in theoretical calculations for anhydrous CA and CA complexes and in experimental results for the complex material of CMC and CA. , The CO stretching peak in the CMCF-F- x hydrogel spectra shifted to lower wavenumber with an increase in the CA concentration increased, i.e., from 1717 cm –1 for CMCF-F-0.05 to 1704 cm –1 for CMCF-F-2 (Figure b). The wavenumber of the CO stretching mode shifts downward owing to an increase in the hydrogen-bond strength. , Thus, the results indicate that the bond strength increased with an increase in the CA concentration.…”
Section: Resultssupporting
confidence: 85%
“…Similar peak shifts have been observed in theoretical calculations for anhydrous CA and CA complexes and in experimental results for the complex material of CMC and CA. , The CO stretching peak in the CMCF-F- x hydrogel spectra shifted to lower wavenumber with an increase in the CA concentration increased, i.e., from 1717 cm –1 for CMCF-F-0.05 to 1704 cm –1 for CMCF-F-2 (Figure b). The wavenumber of the CO stretching mode shifts downward owing to an increase in the hydrogen-bond strength. , Thus, the results indicate that the bond strength increased with an increase in the CA concentration.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The vibrational spectrum of UTSA-16 is quite similar to that collected in the case of the reference compound and does not substantially change upon prolonged activation in a high vacuum till 363 K. By focusing the attention on the most relevant vibrational fingerprints, only IR spectra in the 1670-1500 cm À1 range clearly present the bands due to the n asym (COO À ) mode. 12,13 No bands ascribable to protonated -COOH groups are present, ruling out the presence of Hcit in the structure and all the citrate ligands being fully deprotonated in the material under study. In accordance with that, EDX analysis indicated a K : Co ratio of about 1 : 1.3, suggesting that a possible empirical formula of UTSA-16 here characterized would be K 2 Co 3 (cit) 2 .…”
Section: Resultsmentioning
confidence: 92%